TRANSLATION PROBLEMS OF FASHION INDUSTRY TERMINOLOGY - Волошинович, Наталія (Current Issues of Foreign Philology, 2021)
The article considers the vocabulary of fashion industry as an independent segment in the scientific world image of the native speakers; therefore, it is interesting not only for linguists, but also for non-specialists in the philological sphere. It forms a branched terminology of the design of clothing and fashion, common literary vocabulary and special terms that refer to the concepts of fashion and design of clothing, as well as industrial and creative activities. The article examines the most common methods and techniques for the translation of terms, the main of which are: translation with a lexical equivalent and a non-equivalent translation. Among the main translation techniques of the non-equivalent vocabulary are the following: transcription, transliteration, calque and descriptive translation. A separate part of the article deals with the methods for translation of neologisms, author’s terms, anthroponyms and abbreviations.